Analysis of the degradation of m-cresol with Fe/AC in catalytic wet peroxide oxidation enhanced by swirl flow. (July 2022) - Yao, Chenxing; Jin, Chengyu; Wang, Shengzhe; Wang, Yihuan; Zhang, Yanan; Hou, Zuojun; Yu, Yonghui; Sun, Chenglin; Wei, Huangzhao; Wang, Guowen
Abstract: Catalytic wet peroxide oxidation (CWPO) enhanced by swirl flow (SF-CWPO) was developed for the first time to explore the degradation of m-cresol in 3%iron/activated carbon catalysed Fenton reaction. Under the conditions of catalyst dosage of 0.6 g/L, H2 O2 dosage of 1.5 mL/L, pH = 6 and reaction time of 20 min, the degradation rate of m-cresol and total organic carbon in 100 mg/L m-cresol solution reaches 81.5% and 82%, respectively. The reaction speed in the SF-CWPO system with an independently designed cyclone reactor was two times faster than the traditional CWPO systems. In addition, via liquid chromatography-mass spectrometry analysis of the degradation product, the possible degradation pathway for m-cresol was proposed. The proposed SF-CWPO can potentially be an efficient and economical method to treat organic pollutants in wastewaters. Graphical abstract: Image 1 Highlights: Swirl flow were introduced into catalytic wet peroxide oxidation system to improve the catalytic performance. The SF-CWPO reactor was designed independently and can be scaled up step by step. Centrifugal force and interfacial turbulence in SF-CWPO can improve reaction efficiency and reduce catalyst loss.